Promoting ethical and reproducible cell culture: implementing animal-free alternatives to teaching in molecular and cell biology - Nessar, Alexandra; Röhrs, Viola; Ziersch, Mathias; Ali, Ahmed S. M.; Moradi, Julia; Kurreck, Anke; Berg, Johanna; Kurreck, Jens (Frontiers in Toxicology, 2025)
The widespread use of fetal bovine serum (FBS) and other animal-derived reagents in cell culture raises ethical concerns and scientific limitations, including batch variability and undefined composition. To address these challenges and promote the adoption of xeno-free, human-relevant methods, we developed a graduate-level laboratory course based on animal-free workflows. The curriculum covers key molecular and cell biology techniques: HeLa cell culture and passaging, transfection, RNA interference (RNAi), quantitative RT-PCR (qRT-PCR), dual-luciferase assays, and Western blotting, using reagents selected to exclude animal-derived components. A chemically defined medium (CDM) was optimized for robust HeLa cell growth in the absence of FBS, and recombinant TrypLE was implemented as a substitute for porcine trypsin. Validated non-animal-derived antibodies are also introduced. The course has been successfully piloted and provides a scalable, ethical framework for modern bioscience education. A detailed, open-access protocol enables replication and dissemination. This initiative equips students with practical skills and educational foundation in animal-free methodologies, supporting a shift toward reproducible and ethically responsible biomedical research.